Peran Pendidikan Agama dalam Pembentukan Kesadaran Hukum Peserta Didik - Khaerul, Khaerul; Irwanzah, Muhammad Rafi (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
Religious education plays a strategic role in shaping the character and behavior of students, including in fostering legal awareness. This study aims to analyze how religious education can contribute to the development of students’ legal consciousness within the school environment. Using a qualitative-descriptive method and a literature review approach, this paper demonstrates that religious values such as honesty, justice, responsibility, and obedience to rules are highly relevant in shaping legal attitudes. Effective religious education can serve as a means of internalizing legal values from an early age, which in turn can lead to the emergence of a law-abiding and morally upright generation.